2011
DOI: 10.1289/ehp.1003035
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Brominated Flame Retardants: (In)direct Effects of Parent and Hydroxylated Polybrominated Diphenyl Ethers on the (Developing) Nervous System

Abstract: Background/objective: Polybrominated diphenyl ethers (PBDEs) and their hydroxylated (OH-) or methoxylated forms have been detected in humans. Because this raises concern about adverse effects on the developing brain, we reviewed the scientific literature on these mechanisms.Data synthesis: Many rodent studies reported behavioral changes after developmental, neonatal, or adult exposure to PBDEs, and other studies documented subtle structural and functional alterations in brains of PBDE-exposed animals. Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
243
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(252 citation statements)
references
References 138 publications
(166 reference statements)
2
243
0
Order By: Relevance
“…Recent mechanistic studies have shown that some OH-BDEs are more potent than parent compounds and may contribute substantially to neuro develop mental disorders by direct neuro toxicity, or indirectly through thyroid disruption (Dingemans et al 2008(Dingemans et al , 2010a(Dingemans et al , 2010b(Dingemans et al , 2011Hamers et al 2008;Hendriks et al 2010;Kim et al 2011). In contrast to BDE-47, which showed no activity, 6-OH-BDE-47 and 4´-OH-BDE-49 have been reported to be potent modulators of ryanodine receptors type 1 and 2, which regulate essential aspects of Ca 2+ signaling (Kim et al 2011;Pessah et al 2010).…”
Section: Cyp2b6mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent mechanistic studies have shown that some OH-BDEs are more potent than parent compounds and may contribute substantially to neuro develop mental disorders by direct neuro toxicity, or indirectly through thyroid disruption (Dingemans et al 2008(Dingemans et al , 2010a(Dingemans et al , 2010b(Dingemans et al , 2011Hamers et al 2008;Hendriks et al 2010;Kim et al 2011). In contrast to BDE-47, which showed no activity, 6-OH-BDE-47 and 4´-OH-BDE-49 have been reported to be potent modulators of ryanodine receptors type 1 and 2, which regulate essential aspects of Ca 2+ signaling (Kim et al 2011;Pessah et al 2010).…”
Section: Cyp2b6mentioning
confidence: 99%
“…Recently, hydroxylated metabolites of PBDEs (OH-PBDEs) have been found to accumulate in human serum at levels similar to, and in some cases greater than, that of the parent PBDEs (Athanasiadou et al 2008;Qiu et al 2009). The significance of this finding is heightened by mechanistic studies showing that monohydroxylated metabolites of BDE-47 are more potent than the parent BDE-47 in disrupting Ca 2+ homeo stasis, modulating γ-amino butyric acid (GABA) and α4β2 nicotinic acetylcholine (nACh) receptor function, altering spontaneous activity and cell viability in cultured cortical neurons, and competing with thyroxine (T 4 ) for binding to human trans thyretin (TTR) (Dingemans et al 2008(Dingemans et al , 2010a(Dingemans et al , 2010b(Dingemans et al , 2011Hamers et al 2008;Hendriks et al 2010;Kim et al 2011). Together, these and other studies suggest that bioactivation by oxidative metabolism adds considerably to the neuro toxic potential of PBDEs.…”
mentioning
confidence: 99%
“…For example, some studies report developmental neurotoxicity associated with BDE-209 exposure, including impairment of locomotor activity and cognition (Viberg et al, 2003). Exposure to BDE-209 alters the expression of genes and proteins involved in synapse and axon formation, neuronal morphology, cell migration, and synaptic plasticity (Viberg et al, 2008;Dingemans et al, 2011). In addition, BDE-209 has been shown to cause oxidative stress in neurons, which leads to apoptotic neuronal death (Chen et al, 2010;Costa and Giordano, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that during this period of rapid development, the brain is vulnerable to insults from xenobiotics [7]. Exposure to PBDEs has been associated with developmental neurotoxicity since the beginning of the 21st century [1,8], and the nature of potential adverse effects associated with this exposure continue to be a concern [9].…”
Section: Introductionmentioning
confidence: 99%
“…Brain changes have also been observed in the expression of genes and proteins involved in synapse and axon formation, neuronal morphology, cell migration, and synaptic plasticity [7,11,12]. Cellular and molecular mechanisms affected include neuronal viability (via apoptosis and oxidative stress), neurotransmitter release/uptake, neurotransmitter receptors and ion channels, calcium homeostasis, and intracellular signaling pathways [9]. In humans, studies have shown that adverse effects on cognitive and behavioral performance in children have correlated with maternal serum levels of PBDEs [13].…”
Section: Introductionmentioning
confidence: 99%